Design and development of real-time particulate matter measuring instrument applying laser scattering technique for microenvironment monitoring - Angelo Sean Francis Tiwon (2020)
Particulate Matter (PM) is one of the key indicators in determining Air Quality Index (AQI). While PM has been has identified as one of global health threat by the World Health Organization (WHO), and there is an urgent need for routine air monitoring data on components of the PM mass to identify the role of PM chemical components in causing adverse health effects for exposure control, assessment of particle exposure on a more personal level are not achievable by the conventional method due to their high cost and relatively large size. Therefore, it is crucial to have a better approach in monitoring particulate matter that can provide better spatial and temporal coverage which is made possible with the emergence of low-cost PM sensor. In this study a real time particulate matter measuring instrument applying laser scattering technique was developed and evaluated. Based on the evaluation, PMSA003 was selected as the best sensor to be applied in this PM monitoring instrument due to its high linearity response with reference instruments with R2>0.9 and low intra-model variability of 17.71%. A humidity correction algorithm was developed based on the climate susceptibility test as it was observed there are strong correlation between the reported mass concentration and humidity at more than 65 %RH. To further improve the performance of the instrument, it was deployed in three ambient setting where the density factor for the conversion of particle distribution to mass concentration was obtained for the indoor, outdoor and factory setting. The finalized prototype was validated with the Thermo Scientific™ 1405 TEOM™ Continuous Ambient Particulate Monitor. TOEM is certified Federal Equivalent Method (FEM) instrument by US. Through the field deployment, the prototype showed high correlation with the reference instrument with R2 > 0.9332 for PM2.5 and R2 >0.7623 for PM10.0. In conclusion, an integrated real time particulate matter measuring instrument was designed, developed and evaluated where the term design is referring to the whole system design. The developed instrument shows excellent correlation with reference instruments thus validating its potential to be applied for real life application.